Identifying and testing candidate genetic polymorphisms in the irritable bowel syndrome (IBS): association with TNFSF15 and TNFα - Swan, Caroline; Duroudier, Nathalie P; Campbell, Eugene; Zaitoun, Abed; Hastings, Margaret; Dukes, George E; Cox, Joanne; Kelly, Fiona M; Wilde, Jonathan; Lennon, Mark G; Neal, Keith R; Whorwell, Peter J; et al. (Gut, 2013)
Objectives The postinfectious irritable bowel syndrome (PI-IBS) suggests that impaired resolution of inflammation could cause IBS symptoms. The authors hypothesised that polymorphisms in genes whose expression were altered by gastroenteritis might be linked to IBS with diarrhoea (IBS-D) which closely resembles PI-IBS. Design Part 1: 25 healthy volunteers (HVs), 21 patients 6 months after Campylobacter jejuni infection, 37 IBS-D and 19 IBS with constipation (IBS-C) underwent rectal biopsy for gene expression analysis and peripheral blood mononuclear cell cytokine production assessment. Part 2: Polymorphisms in genes whose expression was altered in Part 1 were assessed in 179 HV, 179 IBS-D, 122 IBS-C and 41 PI-IBS. Results Part 1: Mucosal expression of seven genes was altered in IBS: CCL11, CCL13, Calpain 8 and TNFSF15 increased while NR1D1, GPR161 and GABRE decreased with similar patterns after infection with C jejuni. Part 2: The authors assessed 21 known single nucleotide polymorphisms (SNPs) in these seven genes and one SNP in each of the TNFα and IL-10 genes. Three out of five TNFSF15 SNPs (rs6478108, rs6478109 and rs7848647) showed reduced minor allele frequency (MAF) (0.28, 0.27 and 0.27) in subjects with IBS-D compared with HV (0.38, 0.36 and 0.37; p=0.007, 0.015 and 0.007, respectively) confirming others recent findings. The authors also replicated the previously reported association of the TNFα SNP rs1800629 with PI-IBS which showed an increase in the MAF at 0.30 versus 0.19 for HV (p=0.04). Conclusion IBS-D and PI-IBS patients are associated with TNFSF15 and TNFα genetic polymorphisms which also predispose to Crohn's disease suggesting possible common underlying pathogenesis.